Mobile Application as Platform for Publicly Oriented Government Communications in The Public Services of The Kurdistan Regional Government:: Case Study - Sozan Sulaiman Maghdid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The idea of a "smart city" is thought to apply to overcoming many of the challenges that urban areas in the twenty-first century face. The use of technology in the form of 'mobile government' ('m-government') is thought to connect public needs with government services. Using a mobile application (mobile app) as a medium of government communication is one form of ‘m-government'. This study is based on Mobile apps as a government communication case study, it is conducted by using a web survey (google form) that included many closed type questions as well as a few open type questions directed to the citizens in the Kurdistan region. To analyze the data, we used the (full form of SPSS) version 22 program and the qualitative methods used to assess the validity of this study are interviews and observations. Furthermore, despite the fact that 97.76% of them favor the idea of an e-government, 2.24% of the respondents were against e-government'. The use of mobile apps not only to operate the government's contact function, which serves as a tool for government socialization, but also to serve as a platform for providing public needs in the private and public sectors. The study's most important finding is that mobile applications can be used for public-oriented government communication in Kurdistan Region. Using mobile applications in the sense of good governance will be helped to implement the ideals of inclusion, equality, and transparency